Nonlinear Analysis of Flexible Pile near Undrained Clay Slope under Lateral Loading - Chong Jiang; Yu Li; Lin Liu; Hang Lin (Advances in Civil Engineering)
In this paper, a method is developed for nonlinear analysis of laterally loaded long-flexible pile near undrained clay slope. The ideal elastic-plastic p-y curve model is used as the basic calculation model to study the pile-soil interaction system. To consider the slope effect on the soil resistance along with pile length, related reduction function expressions of soil resistance are selected by assessing the existing methods. A finite difference iteration scheme is proposed to solve the pile’s deflection curve equations to obtain nonlinear response of pile. The developed method is validated by comparing its results with the existing method, which shows a good agreement. A number of parameters analyses are carried out, and effects of different influence factors on laterally loaded pile are further discussed.